No-till farming in the humid and subhumid tropics of Africa - Couper, D.C. (1995)
Tropical soils are generally low in fertility, physically fragile and easily eroded when cleared of natural cover. Cultivation is carried out in the tropics purely for weed control, but this leads to accelerated soil erosion, as cultivated soil) has no protection. Gully erosion can be minimized by the use of graded contour banks. Sheet erosion can be reduced by the use of chemical weed control, as soil cover is maintained in the form of dead mulch and soil disturbance is avoided. This is termed zero-tillage or conservation farming. The frequent use of zero-tillage can lead to soil compaction which can be alleviated with the use of planted leguminous fallows.